2018
DOI: 10.7566/jpsj.87.053001
|View full text |Cite
|
Sign up to set email alerts
|

Slow-Slip Phenomena Represented by the One-Dimensional Burridge–Knopoff Model of Earthquakes

Abstract: Slow-slip phenomena, including afterslips and silent earthquakes, are studied using a one-dimensional Burridge-Knopoff model that obeys the rate-and-state dependent friction law. By varying only a few model parameters, this simple model allows reproducing a variety of seismic slips within a single framework, including main shocks, precursory nucleation processes, afterslips, and silent earthquakes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Shibazaki and Matsu'ura [1993] further found that the accelerating stage from phase-II to phase-III is related to the presence of nucleation phase in the front of the main P wave. Their results are similar to those obtained by Ueda et al [2014Ueda et al [ , 2015 and Kawamura et al [2018]. The results of this study and Wang [2017a] only show two stages which are comparable with the phase-I and phase-III stages proposed by Matsu'ura [1992, 1993].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Shibazaki and Matsu'ura [1993] further found that the accelerating stage from phase-II to phase-III is related to the presence of nucleation phase in the front of the main P wave. Their results are similar to those obtained by Ueda et al [2014Ueda et al [ , 2015 and Kawamura et al [2018]. The results of this study and Wang [2017a] only show two stages which are comparable with the phase-I and phase-III stages proposed by Matsu'ura [1992, 1993].…”
Section: Discussionsupporting
confidence: 91%
“…Brantut et al [2011] concluded that metamorphic dehydration influences the nucleation of unstable slip and could be an origin for slow-slip events in subduction zones. Ueda et al [2014Ueda et al [ , 2015 and Kawamura et al [2018] pointed out that the nucleation process includes the quasi-static initial phase, the unstable acceleration phase, and the high-speed rupture phase (i.e., a mainshock) and recognized two kinds of nucleation lengths, i.e., L sc and L c which are affected by model parameters, yet not by the earthquake size. The L sc related to the initial phase exists only for a weak frictional instability regime; while the L c associated with the acceleration phase exist for both weak and strong instability regimes.…”
Section: Introductionmentioning
confidence: 99%
“…Kawamura et al. (2018) applied a 1‐D multidegree of freedom spring‐slider model with dc=1020.25emnormalm ${d}_{c}={10}^{-2}\,\mathrm{m}$ to reproduce various types of fault slip, such as fast slip, source nucleation, aftershock, and SSE. Our analysis of the tidal response during ETS also supports dc ${d}_{c}$ with the order of 10120.25emnormalm ${10}^{-1\sim -2}\,\mathrm{m}$.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies by Ueda et al revealed that the BK model under the RSF law could describe a slow nucleation process preceding the high-speed rupture of a main shock [41,42], which is not describable by the BK model under the simple velocity-weakening law. Furthermore, recent studies by Kawamura, Yamamoto and Ueda have revealed that the BK model under the RSF law can also describe the slow-slip phenomena including afterslips and silent earthquakes [43] (see also [44]). Afterslips are a long-lasting slow-slip process which takes place following the high-speed rupture of main shock, while silent earthquakes are a slow-slip-only process not accompanying any high-speed rupture nor emission of seismic waves.…”
Section: Introductionmentioning
confidence: 99%